Stress indicators and meat quality of pigs affected by different durations of lairage time - Lukić, Boris; Djurkin, Ivona; Ovničević, D.; Mandić, S.; Didara, Mislav; Šperanda, Marcela; Kušec, Goran (Acta Agraria Kaposváriensis, 2014)
Objective of this study was to investigate the effect of lairage time pigs on stress indicators and meat quality. The study was performed on 90 barrows and gilts divided into three groups according to lairage time: 0 h, 6 h and 24 hours. Blood samples were taken after exsanguination and glucose, lactate, cortisol, as well as activity of creatine kinase were determined. At the slaughter line and in laboratory pH values in ham and LD muscle 45 minutes and 24 h after slaughter, as well as meat colour coordinates (L*, a*, b*), drip loss, cooking loss and instrumental tenderness were measured.. Concentrations of blood stress parameters were highest in the first group (0h lairage time). Statistical analysis showed a significant effect of resting before slaughter on final pH values measured 24 hours after slaughter in ham. Moreover, resting time had a significant effect on L* and a* values and showed tendency to decrease EZ drip (%) as lairage time increased. Pigs slaughtered without rest prior to slaughter showed higher levels of stress and tend to have less desirable meat quality traits.
Keywords: pigs; lairage time; stress; blood parameters; meat quality traits